The effects of debt-to-asset ratio, size of the company, institutional ownership and earnings management on accounting conservatism in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange between 2015 and 2023 - Herdiansyah, Mochamad Ardi; Berliani, Kartika (Economic Reviews Journal, 2024)
This study attempts to ascertain how accounting conservatism is affected in manufacturing businesses in the food and beverage subsector listed on the Indonesia Stock Exchange between 2015 and 2023 by factors such as debt to asset ratio, company size, institutional ownership, and earnings management. This study employs a quantitative methodology that combines a verification and descriptive strategy. Traditional assumption testing, multiple linear regression, Pearson product moment correlation coefficient, determination coefficient, and hypothesis testing with partial and simultaneous tests (f and t tests) are all used in the statistical analysis approach of verification. Sample data comes from 63 financial reports of businesses in the Food and Beverage Manufacturing Subsector. This study employed a purposive sample strategy in conjunction with nonprobability sampling. Version 26.0 of SPSS software is used for data processing. According to preliminary study findings, there is no discernible relationship between accounting conservatism and the debt to asset ratio. Company size has a big impact on accounting conservatism. The impact of institutional ownership on accounting conservatism is negligible at best. Accounting conservatism is neither impacted by or significantly affected by earnings management. The study's findings concurrently demonstrate how the debt to asset ratio, business size, institutional ownership, and earnings management all have an impact on accounting conservatism